2011
DOI: 10.3171/2011.5.focus1196
|View full text |Cite
|
Sign up to set email alerts
|

Cranial vault remodeling for sagittal craniosynostosis in older children

Abstract: Object Sagittal craniosynostosis is the most common form of craniosynostosis and is commonly treated within the first year of life. Optimal treatment of patients older than 1 year of age is not well characterized. The authors reviewed cases of sagittal craniosynostosis involving patients who were treated surgically at their institution when they were older than 1 year in order to determine the rate of intracranial hypertension (ICH), potential to develop nonhealing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…23,24 Follow-up varied from 6 to 264 months after surgery and was done either by palpation, 20,25 using radiology 16,26 or both. 21,27 (Table 1) In several studies, the type of follow-up was unclear. 5,17,24,28 Higher age of the patient at surgery is associated with incomplete reossification, 7,16,20,24,[29][30][31][32][33][34] but only a few studies have systematically examined and suggested its relation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…23,24 Follow-up varied from 6 to 264 months after surgery and was done either by palpation, 20,25 using radiology 16,26 or both. 21,27 (Table 1) In several studies, the type of follow-up was unclear. 5,17,24,28 Higher age of the patient at surgery is associated with incomplete reossification, 7,16,20,24,[29][30][31][32][33][34] but only a few studies have systematically examined and suggested its relation.…”
Section: Resultsmentioning
confidence: 97%
“…7,8,25,27,41,51,17 In the case of late referral, it is essential for the surgical team to know whether it can rely on spontaneous reossification. In fact, many centers do not leave reossification to chance and fill the bony gaps with some sort of material.…”
Section: Reasons For Incomplete Reossification Age At Surgerymentioning
confidence: 99%
“…Despite the lack of specific diagnostic criteria required for pre-mortem clinical diagnosis, patients afflicted with CTE diagnosed post-mortem are often described as suffering behavioral, cognitive, and emotional changes or impairments prior to death (Gavett et al, 2011b; Omalu et al, 2011b; Saulle and Greenwald, 2012). Notably, symptom development occurs following a prolonged latency in most cases, although exceptions do exist (Gavett et al, 2011a; Omalu et al, 2011b). The tendency for a latent period creates a clear distinction between initial symptoms associated with traumatic brain injury (TBI) and the persistent, long-term degeneration, much like other neurodegenerative diseases such as Alzheimer’s disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic traumatic encephalopathy has been diagnosed in a broad spectrum of individuals with a history of head trauma, although the number of and severity of impacts is often unclear, ranging from athletes playing American football, soccer, hockey, boxers, and wrestlers to soldiers who have received battlefield injuries (Omalu et al, 2005, 2006, 2010a,b,c, 2011b; McKee et al, 2009; Baugh et al, 2012; Goldstein et al, 2012; Lakhan and Kirchgessner, 2012). Due to the variety of individuals afflicted by CTE, emerging evidence indicates that CTE is likely more common than previously thought (Stern et al, 2011; Baugh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical techniques exist for the correction of sagittal synostosis; however, there are no current standardized management guidelines [2,3]. When diagnosed and treated after the first year of life, the surgical management of sagittal synostosis typically necessitates total cranial vault reconstruction [4][5][6][7]. The safety of total cranial vault reshaping has improved greatly over the past 3 decades, and common complications include infection, subgaleal hematoma, dural tear, wound breakdown, electrolyte abnormalities, hydrocephalus, and postoperative coagulopathy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%